2011
DOI: 10.1093/mp/ssr039
|View full text |Cite
|
Sign up to set email alerts
|

Divergent DNA Methylation Patterns Associated with Abiotic Stress in Hevea brasiliensis

Abstract: Cytosine methylation is a fundamental epigenetic mechanism for gene-expression regulation and development in plants. Here, we report for the first time the identification of DNA methylation patterns and their putative relationship with abiotic stress in the tree crop Hevea brasiliensis (source of 99% of natural rubber in the world). Regulatory sequences of four major genes involved in the mevalonate pathway (rubber biosynthesis pathway) and one general defense-related gene of three high-yielding popular rubber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 65 publications
6
41
0
Order By: Relevance
“…DNA methylation can be found on CpNpG islands and non-symmetrical trinucleotides in addition to cytosine of CpG islands (Pradhan et al, 1999;Lindroth et al, 2001;Cao and Jacobsen, 2002). Abiotic stress-induced methylation is thought to be associated with various biochemical pathways involved in plant adaptation and stress responses (Uthup et al, 2011). As demonstrated in this study, one CpG island is present in the promoter of GRMZM2G300348_T02, T03, T04 covering almost all promoter regions, suggesting an important role for DNA methylation in the transcriptional regulation of the expression of these transcripts.…”
Section: Discussionsupporting
confidence: 50%
“…DNA methylation can be found on CpNpG islands and non-symmetrical trinucleotides in addition to cytosine of CpG islands (Pradhan et al, 1999;Lindroth et al, 2001;Cao and Jacobsen, 2002). Abiotic stress-induced methylation is thought to be associated with various biochemical pathways involved in plant adaptation and stress responses (Uthup et al, 2011). As demonstrated in this study, one CpG island is present in the promoter of GRMZM2G300348_T02, T03, T04 covering almost all promoter regions, suggesting an important role for DNA methylation in the transcriptional regulation of the expression of these transcripts.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, we tend to think, that al− though the population from Arctowski Station is less variable at the genetic level (possibly due to founder or bottleneck effects), the increase of epigenetic varia− tion in the Antarctic population may point out a response to external stress fac− tors. It could be induced by environmental stimuli (Chinnusamy and Zhu 2009;Boyko and Kovalchuk 2011;Uthup et al 2011) such as e.g. cold (Stewards et al 2002, water (Labra et al 2002), and/or osmotic (Tan 2010) stresses (Bruce et al 2007), commonly experienced by organisms under polar condition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, binding sites for MADS-box transcription factor, RIN, one of the main ripening transcription factors, are frequently localized in the demethylated regions of the promoters of numerous ripening genes, and it is suggested that its binding to these sites occurs in concert with demethylation (Chen, et al 2015). Besides development, growing evidences have suggested a role of DNA methylation in the regulation of gene expression during abiotic stress responses (Chinnusamy and Zhu 2009, Dowen et al 2012, Garg et al 2015, Shaik and Ramakrishna 2012, Uthup et al 2011. Likewise, biotic stress such as pathogenic infection resulted in genome-wide hypermethylation, and resistance-related genes were hypomethylated in plants (Peng and Zhang 2009).…”
Section: Introductionmentioning
confidence: 99%